Overlooked coastal habitats expose a new species: Ochthebius vilanovensis sp. nov. (Coleoptera, Hydraenidae) - Villastrigo, Adrián; García-Esquivel, Eva (Zootaxa, 2024)
We describe a new water beetle species, Ochthebius vilanovensis sp. nov., from supralittoral coastal crevices on the northern Mediterranean coast of Spain. Detailed morphological and molecular analyses reveal significant divergence from closely related species, highlighting its taxonomic status. This discovery emphasises the ecological importance of supralittoral habitats and suggests the potential for uncovering additional, cryptic species in these environments.